Usefulness and limitation of DDD and PDD analyses. 12 months of solid oral antipsychotics prescribing data for the NHS-reimbursed treatment of schizophrenia in Italy - Pradelli, Lorenzo (Farmeconomia. Health economics and therapeutic pathways, 2008)
The estimation of real-world pharmaceutical costs in a given setting is one of the crucial steps in pharmacoeconomic comparisons among drugs used in that setting. For the purpose of this estimation, information regarding available pharmaceutical forms, alongside price and market share, for every considered drug is needed. Furthermore, it’s necessary to know, at least approximately, drug quantities averagely consumed in each episode, in the case of acute therapies, or on a daily basis in chronic therapies. This data is difficult to measure in non-experimental settings, and is generally approximated using the statistical average of the drug quantity prescribed by physicians for a given condition. This paper will briefly review definitions and appropriate uses of DDDs (defined daily dose), and PDDs (prescribed daily dose), and then illustrate the expressed concepts on the basis of a practical example constructed on the analysis of last available 12 months of solid oral antipsychotics prescribing data for the NHS-reimbursed treatment of schizophrenia in Italy.